2019
DOI: 10.1172/jci.insight.130540
|View full text |Cite
|
Sign up to set email alerts
|

BCG revaccination boosts adaptive polyfunctional Th1/Th17 and innate effectors in IGRA+ and IGRA– Indian adults

Abstract: BACKGROUND. Bacille Calmette-Guérin (BCG) vaccine is protective against Tuberculosis (TB) in children, but its efficacy wanes with age. Consequently, determining if BCG revaccination augments anti-TB immunity in young adults in TB endemic regions is vital. METHODS. Two hundred healthy adults, BCG vaccinated at birth, were tested for their IFN-γ release assay (IGRA) status. Of these, 28 IGRA + and 30 IGRAwere BCG revaccinated, and 24 IGRA + and 23 IGRAsubjects served as unvaccinated controls. T and innate cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 80 publications
12
76
1
Order By: Relevance
“…Bacille Calmette-Guérin or BCG vaccination policy implementation by countries and its coverage had been proposed to lower the COVID-19 cases and mortality [REFs in [1][2][3][4]. The BCG vaccination given to children and adults has been known to protect them from many unrelated pathogens and diseases [REFs in 1,3, 5-10 ] supposedly through the generation of 'trained immunity' and heterologous cell-mediated immunity (e.g., Th1 and Th17) that last for a variable period [1,5,[9][10][11][12]. However, the confounding variables among the countries for COVID-19 such as the stage of the outbreak, population age distribution, health infrastructure, management practices, the testing/screening, and reporting guidelines, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bacille Calmette-Guérin or BCG vaccination policy implementation by countries and its coverage had been proposed to lower the COVID-19 cases and mortality [REFs in [1][2][3][4]. The BCG vaccination given to children and adults has been known to protect them from many unrelated pathogens and diseases [REFs in 1,3, 5-10 ] supposedly through the generation of 'trained immunity' and heterologous cell-mediated immunity (e.g., Th1 and Th17) that last for a variable period [1,5,[9][10][11][12]. However, the confounding variables among the countries for COVID-19 such as the stage of the outbreak, population age distribution, health infrastructure, management practices, the testing/screening, and reporting guidelines, etc.…”
Section: Introductionmentioning
confidence: 99%
“…(environmental or BCG) could help reduce COVID-19 infections or mortality in a population, the estimated prevalence of the tuberculin immunoreactivity or the so-called “% LTBI” [ 21 ] of resident populations would closely correlate with COVID-19 infection and mortality rates regardless of the BCG vaccination policy, BCG coverage, or its implementation among countries [ 22 ]. The European countries that have quite a mix of diverse BCG vaccination policies—ranging from none ever to current universal vaccination [ 22 ], relatively comparable medical infrastructure, mobility, exposure to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), and other confounding variables and more importantly currently at a similar stage of epidemic curve, i.e., postinfections peak, but could have differential “trained immunity” and cell-mediated immunity status as may be supposed from % LTBI prevalence [ 5 , 6 , 7 , 12 ], offer an excellent opportunity to evaluate such an assertion.…”
Section: Commentarymentioning
confidence: 99%
“…It must be remembered that BCG vaccination does not necessarily elicit a cell-mediated immune response in all, at the same rate, and there is also reported loss with age, absence of rechallenge, and immune suppression. In the view of the observation presented, it may be suggested that ongoing trials/studies evaluating the effect of BCG vaccination on COVID-19 infections [ 1 , 13 ], including the one recently concluded in Israel and reported in JAMA [ 14 ], could provide more objective conclusions on inclusion of the estimates about the “trained immunity” and heterologous cell-mediated immune response of study participants/ populations [ 5 , 12 ].…”
Section: Commentarymentioning
confidence: 99%
“…In mice, wP and adjuvanted intranasal pertussis vaccines induced Th17 responses and showed higher efficacy against nasal infection than an aluminium-adjuvanted aP vaccine 63,64 . BCG revaccination of adults in India was also shown to boost antimycobacterial Th1/Th17 responses 65 . This, in combination with evidence that BCG revaccination prevented sustained seroconversion by IFN-γ release assay infection in a South African study 66 , may suggest an association between successful induction of Th1/ Th17 and prevention of Mtb infection.…”
Section: Determinants Of Vaccine Designmentioning
confidence: 99%
“…The protective adaptive response is thought to be mediated mainly by CD4+ Th1 cells with contributions from Th17 and CD8+ T-cells, but as yet no solid explanation how bacterial killing is finally achieved is forthcoming 116,117 . Recent findings from India using BCG revaccination in IGRA+ (IFN-y release assay linked to presence of Mycobacteria) subjects demonstrated boosting of Th1/Th17 CD4+ T-cell responses including polyfunctional T-cells 65 . BCG prevented sustained seroconversion (by IFN-γ release assay) in South African adolescents when given as a booster 66 .…”
Section: S Aureusmentioning
confidence: 99%